Teaching and Learning in the Age of Artificial Intelligence: Towards an Integrated Approach to Digital Literacy in Algerian Higher Education - Aboura, Bouchra (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2025)
In recent years, Algerian universities have faced a new challenge: adapting to the rapid rise of artificial intelligence while still closing long-standing digital gaps. This contribution looks at how digital literacy is evolving in higher education through national strategies, local policies, and direct engagement with faculty members. Based on policy texts, institutional reports, and hands-on experience supporting faculty development, it sheds light on the gap between national ambitions and the everyday realities encountered by teachers and students. While new platforms and tools are being deployed, key challenges remain: limited infrastructure, lack of training, and the uncritical use of AI tools in learning environments. Rather than treating digital transformation as a purely technical shift, this paper argues for a broader, more grounded approach, one that includes training, ethical reflection, and adaptation to each academic discipline. A practical roadmap is proposed to help institutions move forward: start with training, provide clear frameworks, and adapt strategies to local needs and contexts. At its core, this reflection suggests that meaningful change in education doesn’t begin with tools, but with people. Supporting teachers and students in thoughtful, inclusive ways is essential if AI is to serve learning, rather than replace it.